Rules for the publication of manuscripts in scientific, peer-reviewed, journal “Cardiovascular Therapy and Prevention” - article Editorial (Кардиоваскулярная терапия и профилактика, 2016)
Rules for the publication of manuscripts in scientific, peer-reviewed, journal “Cardiovascular Therapy and Prevention”